Biological interactions in restoration: the case of Tecoma stans (Bignoniaceae) and mycorrhizal fungi - Becerril-Navarrete, Arubi; Gómez-Romero, Mariela; Lindig-Cisneros, Roberto; Blanco-García, Arnulfo; Villegas, Javier; Pineda-García, Fernando (Instituto de Ecología, A.C., 2022)
Background and Aims: Anthropogenic or natural disturbances can be so strong that intervention is required to recover degraded sites. One way to facilitate the recovery is the use of native species adapted to the local environment; however, there is lack of knowledge about their performance. Additionally, the establishment of interactions with mycorrhizal fungi would contribute to greater success in survival and growth of plant species used in restoration efforts. Tecoma stans is a native shrub with potential for restoration as it is considered to be stress resistant. Therefore, in the present study we explored if the species sustained interactions with mycorrhizal fungi and a bacterium and if this impacts its growth. Methods: We established an experiment in a semi-controlled environment, seeds were germinated and the seedlings were inoculated with mycorrhizal fungi (Rhizophagus intraradices, Pisolithus arhizus and Scleroderma verrucosum) and a bacterium (Azospirillum brasilense). After six months of growth in the inoculum treatments we measured the seedling relative growth rate, we quantified root and leaf morphofunctional traits and we explored the degree of infection in the roots. Key results: We detected that all fungi infected the plants and each one had different effects in the seedling growth and in its morpho-functional traits. The inoculation with S. verrucosum had positive effects on growth, and the seedlings had larger leaves and a larger canopy, a root system of greater volume and roots of larger diameter. Conclusions: Our results indicate that the use of mycorrhizal fungi would contribute to the success of the establishment of T. stans in restoration plans, since they promote growth and characteristics that potentially allow the species to realize a greater resource capture.